Wolves respond differently to human cues as they expand into urban landscapes - Martina Lazzaroni; Rudy Brogi; Francesca Brivio; Elena Bassi; Andrea Boromello; Tabea Teichmann; Friederike Range; Marco Apollonio; Sarah Marshall-Pescini (Proceedings of the National Academy of Sciences, 2026)
Wolves ( Canis lupus ) recolonizing human-dominated landscapes encounter anthropogenic risks and opportunities, but how this shapes their fear of humans is unknown. We tested 185 individually identified wild wolves across 44 locations covering a wide urbanization gradient, exposing them to novel objects and human playbacks. Wolves from more urbanized areas showed reduced fear at first exposure to an object but heightened caution when the object changed, indicating increased attention to environmental changes, rather than uniform fear reduction. By contrast, playbacks of human voices elicited strong fear responses (>80%), regardless of urbanization. However, individuals habituated to both stimuli quickly and at a similar pace, highlighting their rapid learning abilities. Sociality buffered fear, with wolves in groups reacting less fearfully than wolves alone. Results show that wolves are capable of flexibly modulating their behavioral responses to both the risks and opportunities of human-dominated landscapes, which likely underpins their urban success and requires us to rise to the challenge of peaceful coexistence.